HUBUNGAN KECERDASAN EMOSI DENGAN KEMANDIRIAN ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA 3 KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Zulhelda Zulhelda; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is backed by the independence of the child. Each child has different levels of emotional intelligence in the face of a problem in his life, where the child with emotional intelligence will have a good self control, a sense of responsibility for himself or to overcome the problems faced. This research aims to know the relationship of emotional intelligence with the independence of children aged 5-6 years in TK Negeri Pembina 3 subdistrict Marpoyan Damai Kota Pekanbaru. This research is quantitative research with the type of correlation study. As for the population of this research of 100 children, the sample of this study was as much as 100 children. The data collection techniques used are observations. Data analysis techniques using Person Product Moment correlation technique. It is seen from the overall number of emotional intelligence indicators in the category with a percentage of 57.30% while on the child's self-reliance indicator with a percentage of 64.57%. Based on a known hypothesis test of a correlation coefficient value of rxy = 0.361 and the equivalent significance of 0.000 < 0.05. Thereby, the level of relationship between emotional intelligence and child independence belongs to the low.Key Words: Emotional Intelligence, Child Independence